Two new species of Cyanopenthe Nikitsky from Taiwan (Coleoptera, Tetratomidae, Penthinae) - Hsiao, Yun; Pollock, Darren A.; Barclay, Maxwell V. L. (Zootaxa, 2015)
Two new species of Cyanopenthe Nikitsky, 1998 are described from Taiwan, under the names of Cyanopenthe taiwana sp. nov. and Cyanopenthe leei sp. nov., representing the first documented occurrence of the genus in Taiwan. Descriptions of both species, including the first description of males of Cyanopenthe, are supplemented with photos of habitus, antennae and abdomens of females, and illustrations of pronotum, genitalia of both sexes and abdominal ventrite V of females. Additionally, for Cyanopenthe metallica (Champion, 1916), photos of habitus and antenna of the holotype, supplementary description and illustrations of genitalia and abdominal ventrite V of females are provided. A key for the identification of Cyanopenthe species is given.